Wira Chandra New Music Creation | Musik Kreasi Baru Wira Chandra - I Made Dwi Rustika Manik; I Nyoman Sudiana; Ni Putu Hartini (GHURNITA: Jurnal Seni Karawitan, 2021)
The composition of Wira Chandra is inspired by the characteristics of a teacher who is teaching his students, the stylist is interested in bringing the event into a work idea that will be transformed into a slick and spectacular musical composition. Wira Chandra is a warrior who has a strong personality and an attitude of compassion by interpreting ideas from the characteristics of a teacher. Creating a work of Wira Chandra's art will be poured into one of the Balinese gamelan expression media, namely Gong Kebyar. Wira Chandra's compositional work is a slow composition inspired by the character of a teacher who is packaged into a creative slow dance using the basic Tri Angga Pegongan structure, and the stylist breaks down the structure into Kawitan, Pengawak, Pengisep, Pengcet, Ngembat and Pekaad, beat egg or mad. The realization of Wira Chandra's work is through a creative process which is divided into three stages, namely exploration, improvisation, and forming.